Prevalence, Activity Limitations and Quality of Life in Patients with Non-Specific Neck Pain in Burundi: A Cross-Sectional Study [Response to Letter] - Ndacayisaba G; Ndayishima B; Mapinduzi J; Ndayishimiye P; Sinzakaraye A; Van Cant J (Journal of Pain Research)
Gérard Ndacayisaba,1,2 Bénit Ndayishima,3 Jean Mapinduzi,2,4,5 Pierre Ndayishimiye,1,2 Alexis Sinzakaraye,3,6 Joachim Van Cant7 1CNRKR - Centre National de Référence en Kinésithérapie et Réadaptation médicale, Bujumbura, Burundi; 2TechnoRehab Lab2, Filière de Kinésithérapie et Réadaptation, Institut National de Santé Publique, Bujumbura, Burundi; 3Département de Médecine Physique et Réadaptation, Centre Hospitalo-Universitaire de Kamenge, Bujumbura, Burundi; 4CKAO-AMAHORO - Cabinet de Kinésithérapie et d’Appareillage Orthopédique, Bujumbura, Burundi; 5REVAL Rehabilitation Research Center, Faculty of Rehabilitation Sciences, Hasselt University, Diepenbeek, Belgium; 6CAMERHU - Cabinet Médical de Rhumatologie, Bujumbura, Burundi; 7Unité de Recherche en Sciences de la Réadaptation/Rehab Lab, Faculté des Sciences de la Motricité Humaine, Université Libre de Bruxelles, Bruxelles, BelgiqueCorrespondence: Gérard Ndacayisaba, CNRKR - Centre National de Référence en Kinésithérapie et Réadaptation médicale Bujumbura, Burundi, Tel +257 61 355 482, Email ndacayisaba199065@gmail.com